The genus Cassia L.: Ethnopharmacological and phytochemical overview. (4th December 2020) - Khurm, Muhammad; Wang, Xingbin; Zhang, Hui; Hussain, Sajid Nawaz; Qaisar, Muhammad Naeem; Hayat, Khezar; Saqib, Fatima; Zhang, Xinxin; Zhan, Guanqun; Guo, Zengjun
Abstract : Nature gifts medicinal plants with the untapped and boundless treasure of active chemical constituents with significant therapeutic potential that makes these plants a beneficial source in the development of phytomedicines. Genus Cassia, with approximately 500 species, is a large group of flowering plants in the family Fabaceae. Cassia species are widely distributed throughout different regions mainly tropical Asia, North America, and East Africa. In the folk medicinal history, these plants are used as laxative and purgative agents. In the Ayurveda system of medicine, they are used to cure headache and fever. Cassia plants exhibit pharmacological activities at large scales such as antimicrobial, anticancer, antiinflammatory, antioxidant, hypoglycemic, hyperglycemic, antimutagenic, and antivirals. The phytochemical investigations of genus Cassia demonstrate the presence of more than 200 chemical compounds, including piperidine alkaloids, anthracene derivatives (anthraquinones), flavonoids, pentacyclic triterpenoids, sterols, phenylpropanoids, and γ‐naphthopyrones. The literature illustrated anthraquinones and flavonoids as major secondary metabolites from this genus. However, some Cassia plants, with rich contents of anthraquinones, still show toxicology properties. As Cassia plants are used extensively in the herbal system of medicine, but only senna dosage forms have achieved the status of the pharmaceutical market as standard laxative agents. In conclusion, further investigations on isolating newer biologically active constituents, unknown underlying mechanisms, toxicology profiles, and clinical studies of Cassia species are needed to be explored. This review article specifies the systematic breach existing between the current scientific knowledge and the fundamentals for the marketization of genus Cassia products.